A Native Mobile-Based App for Nutritional Self-Care Behavior Assessment : Assessment of A Mobile Nutritional Application - Jamshidnezhad, Amir; Mousavi Jazayeri, Seyed Mohammad Hossein; Fouladi Dehaghi, Behzad; Talebi Shoushtarian, Ali (Progress in Nutrition, 2021)
Background: While obesity and weight mismatch are of the commonest health challenges worldwide, the advancement of mobile technology and its entry into the field of health have proven to have a significant role in weight control and self-care in nutritional behavior. Purpose: the purpose of the study was to develop and evaluate an integrated communication app on the nutritional behavior of users and their opinion of the app usability. Methods: Fit-mail App for Nutritional Self-care (FANS) was developed according to the app development methodology including design, implementation, and evaluation phases. The FANS was provided to 50 students of Ahvaz University of Medical Sciences who voluntarily participated in the study. Nutritional behavior was examined using the FANS during two stages before and after a 60-day period. The usability and nutrition activity were assessed in the students who completed the intervention of a mobile app on the nutritional behavior study. Results: The results showed statistically significant differences between the two questionnaires before using FANS with mean = 61.7292 and after that mean = 92.1042 (p-value